Frontispiece: Magnetic Switching by the In Situ Electrochemical Control of Quasi‐Spin‐Peierls Singlet States in a Three‐Dimensional Spin Lattice Incorporating TTF‐TCNQ Salts. Issue 17 (25th March 2018) - Fukunaga, Hiroki; Tonouchi, Masanori; Taniguchi, Kouji; Kosaka, Wataru; Kimura, Shojiro; Miyasaka, Hitoshi
Abstract : Hiding a specific function of a material using a masking trigger (i.e., function inactivation) and then triggering the functionality by applying an external stimulus is a unique way to bring on‐demand functionality to a molecular system. We demonstrate magnetic phase control by combining the pre‐organization of trigger (i.e., "spin‐Peierls"‐like spin singlet formation incorporated in a porous magnetic framework) and a post‐treatment (i.e., electrochemical reduction using a Li‐ion battery cell) for triggering the magnetic long‐range correlation through the framework. For more information, see the Full Paper by H. Miyasaka onpage 4294 ff.